2020
DOI: 10.1016/j.cbpa.2019.110588
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of brilliant blue FCF across the Drosophila midgut and Malpighian tubule epithelia

Abstract: Under conditions of stress, many animals suffer from epithelial barrier disruption that can cause molecules to leak down their concentration gradients, potentially causing a loss of organismal homeostasis, further injury or death. Drosophila is a common insect model, used to study barrier disruption related to aging, traumatic injury, or environmental stress. Net leak of a non-toxic dye (Brilliant blue FCF) from the gut lumen to the hemolymph is often used to identify barrier failure under these conditions, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This is reminiscent of the overall alteration of controlled epithelial permeability broadly affecting living organisms during ageing 75 . The recent demonstration that the Smurf phenotype is due to increased intestinal permeability but also to decreased Malpighian tubules activity 76 is supportive of organismal functional failure occurring in the Smurf phase. Whether it is what is called multivisceral failure in humans is under investigation, but it might highlight the use of the Smurf model of ageing for the study of other barriers, especially the BBB.…”
Section: Discussionmentioning
confidence: 96%
“…This is reminiscent of the overall alteration of controlled epithelial permeability broadly affecting living organisms during ageing 75 . The recent demonstration that the Smurf phenotype is due to increased intestinal permeability but also to decreased Malpighian tubules activity 76 is supportive of organismal functional failure occurring in the Smurf phase. Whether it is what is called multivisceral failure in humans is under investigation, but it might highlight the use of the Smurf model of ageing for the study of other barriers, especially the BBB.…”
Section: Discussionmentioning
confidence: 96%
“…1). For both Drosophila [39,65,66] and Locusta [67] it has been shown that epithelial barrier function is reduced at low temperature causing increased leak in cold sensitive species (Fig. 3A).…”
Section: The Influence Of Thermal Acclimation and Adaptation On Osmor...mentioning
confidence: 99%
“…This experimental setup of a water or ice bath can also be utilized for the opposite thermal conditions of low temperatures [ 110 , 111 , 112 ].…”
Section: Phenotyping Of D Melanogastermentioning
confidence: 99%